2019
DOI: 10.1111/jonm.12780
|View full text |Cite
|
Sign up to set email alerts
|

Nurses leadership in research and policy in Nigeria: A myth or reality?

Abstract: Aim This study evaluates nurses' leadership in research and policy formulation in southern Nigeria. Background In Africa and particularly in low‐ and middle‐income countries, expected health information from nurse's leaders is sometimes not available, thereby hindering the attainment of sustainable health. Methods This qualitative study used 12 high‐ranking nurses leader from primary, secondary and tertiary health care systems in Cross River State, Nigeria. In‐depth interview and focus group discussion were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The challenges to political participation and in policy making were addressed in 17 studies (AbuAlRub & Foudeh, 2017; Ahoya, Abhichartibuttra, & Wichaikhum, 2016; Anderson, Bruce, Edwards, & Podham, 2016; Asuquo, 2019; Asuquo, Etowa, Gifford, & Holmes, 2016; Avolio, 2014; Cramer, 2002; Ditlopo, Blaauw, Penn‐Kekana, & Rispel, 2014; Hughes, 2010; Juma et al, 2014; Kunaviktikul et al, 2010; Kung & Rudner Lugo, 2015; Richter et al, 2013; Salavador, 2010; Shariff, 2014; Vandenhouten, Malakar, Kubsch, Block, & Gallagher‐Lepak, 2011; Warner, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The challenges to political participation and in policy making were addressed in 17 studies (AbuAlRub & Foudeh, 2017; Ahoya, Abhichartibuttra, & Wichaikhum, 2016; Anderson, Bruce, Edwards, & Podham, 2016; Asuquo, 2019; Asuquo, Etowa, Gifford, & Holmes, 2016; Avolio, 2014; Cramer, 2002; Ditlopo, Blaauw, Penn‐Kekana, & Rispel, 2014; Hughes, 2010; Juma et al, 2014; Kunaviktikul et al, 2010; Kung & Rudner Lugo, 2015; Richter et al, 2013; Salavador, 2010; Shariff, 2014; Vandenhouten, Malakar, Kubsch, Block, & Gallagher‐Lepak, 2011; Warner, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchical gender power structure that has preferred men over nurses in authoritative positions has undermined the role and participation of nurses in politics and political decision making at the organizational and systematic levels (Ahoya et al, 2016; Hughes, 2010). Studies reported the preference of male physicians over nurses, physicians being more vocal than nurses on policy forums, and purposeful neglect of nurses’ opinions (Asuquo, 2019; Hughes, 2010; Shariff, 2014). Nurses also reported inadequate support from the political sector, government officials, or professional organizations (Kunaviktikul et al, 2010; Richter et al, 2013) due to their negative public image (Shariff, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations